Chinese Consumer Ethnocentrism: A Field Experiment - Bi, X.; Gunessee, S.; Hoffmann, R.; Hui, Wendy; Larner, J.; Ma, Q.; Thompson, F. (John Wiley & Sons Ltd., 2012)
Consumer ethnocentrism presents barriers for internationalising organisations. In China, evidence of a resurgent nationalism partly fuelled by rapid economic growth portends a shift in consumption away from foreign towards domestic products. On the other hand, rising consumer demand for branded and luxury products cannot be fully met domestically. However, much of the available evidence on Chineseconsumer ethnocentrism is anecdotal and is based on attitudinal surveys that, as accurate measures of actual purchasing behaviour, suffer from certain methodological issues. In response, we report an experiment that measures the ethnocentrism of 447 Chinese consumers as their incentive-compatible choices between foreign and domestic products in a field setting. Our findings show little effect of foreignorigin on subjects’ choices that were only weakly related with attitudinal measures including the commonly used consumer ethnocentric tendencies scale (CETSCALE). Our results question the existence of ethnocentric consumer behaviour in China and the use of CETSCALE to gauge it generally.